ANALISA KEBIJAKAN AMERIKA SERIKAT, CINA, DAN RUSIA DALAM KESEPAKATAN NUKLIR IRAN - Imam Mahdi (Jisiera: The Journal of Islamic Studies and International Relations, 2016)
Iran and P5+1 (Cina, France, Russia, the United Kingdom, and the United States; plus Germany) reached agreement on June 2015 for Iranian nuclear issue. It had taken time more than thirteen years since Iran started its program. In the one side, this agreement succeeded due to Iranian politic and economic changes. In the other side, this deal succeeded because the United States changed its policy towards Iran under Obama’s regime. Russia and Cina also supported that deal while they were hoping the lifting of all sanctions.